Il soffitto delle Sibille nel palazzo del cardinale Della Valle a Roma - Grieco, Lorenzo (Opus Incertum, 2018)
The survey and the analysis of the luxury setup in a building can be decisive in reconstructing the function and the spatial succession of its interior rooms. Wooden ceilings, which are representative objects as well as technological devices, share this vocation. The paper considers the ceilings of the Roman palace of cardinal Andrea della Valle (1463-1534), which clarify the distributional changes affecting the building through time. Particularly, the opulence and the orientation of the coffers in the first landing suggest the use of this space as a vestibule. The entire layout of the piano nobile should be considered according to a different distribution. Therefore, the current antechamber, known as the room of the Sibyls because of the painting on the ceiling, was used as a private chapel, as suggested by the theme of the decorations. The stylistic analysis of the Sibyls and the comparison with some artworks from the 16th century made possible their attribution to Francesco Salviati (1510-1563). Furthermore, the existence of three tables on the same subject led to new considerations regarding their history.